THE USE OF SLANG IN SELECTED SONGS BY BLACK EYED PEAS LYRICS - Nuraida, Nuraida; Halim, Abd (Journal of English Literature and Linguistic Studies, 2023)
The researchers obtained several points that could lead to an easier understanding of this research. In this finding, there are 4 types of the slang: blending, someone’s nicknames, shortened sentences, and society slang. The most dominant type in the findings of this study is the type of society slang with 15 data from 35 slang data found, and the least type of slang found in the lyrics of the song is the blending type as many as 5 slang from 35 slang data in the findings. The second is the slang function in the lyrics of the black eyed peas’ song. The functions that have been set as many as 14 functions: Makes a Humor, look different/follow a trend, look picturesque, attract attention, to avoid cliches, to the point/shortened sentences, increase vocabulary, avoid words that are always used, talk and to write, to make it easier to interact in social, to induce friendliness or intimacy, shows not part of the group, identity of a certain group, to be Secret. The dominant slang function is shortened word or to the point as much as 7 data from 35 slang found. And the last is the meaning that has been explained using several trusted dictionaries.